Focusing on a complete blood cell parameter: mean platelet volume levels may be a predictor of coronary slow flow - Yilmaz, Mucahid; Dagli, Mustafa Necati; Uku, Okkes; Bilen, Mehmet Nail; Korkmaz, Hasan; Erdem, Kenan; Kurtoglu, Ertugrul (Dove Medical Press Ltd, 2017)
Background: The relationship between increased mean platelet volume (MPV) and atherosclerosis is well known. In the present study, MPV in patients with coronary slow flow (CSF) and in cases with normal coronary anatomy (NCA) was investigated and compared with the aim of identifying the relationship between CSF and MPV. Patients and methods: We studied 40 patients previously determined via coronary angiography as having NCA and 40 patients with CSF in the coronary blood stream, as identified by thrombolysis in myocardial infarction square. Thus, a total of 80 patients from the Elazig Education and Research Hospital (Elazig, Turkey) were included in the present study retrospectively and laboratory and anamnesis information was scanned into their files. The relationship between MPV and CSF was studied. Results: MPV levels were observed to be significantly higher in the CSF group compared to the NCA group (10.05 +/- 1.3 and 8.6 +/- 0.6, p<0.001). In receiver operating characteristics analyses, it was determined that an MPV > 9.05 measured in CSF patients at application had a predictive specificity of 77.5% and sensitivity of 77.5% for CSF ( area under the curve: 0.825, 95% confidence interval [CI]: 0.726- 0.924, p< 0.0001). It was found that MPV level was an independent predictor of CSF (beta=-600, p<0.001, 95% CI: -0.383 to -0.176). Conclusion: MPV is increased in patients with CSF when compared to patients with NCA. This finding supports the fact that MPV could be a predictor of CSF.
Keywords: coronary slow flow; mean platelet volume; atherosclerosis